Comparative Analysis of sn-2 Palmitic Acid Distribution in Commercially Available Infant Formula Using High Performance Liquid Chromatography with Evaporative Light-Scattering Detector - JIANG Xueming, ZHANG Wendi, LI Chuan, LI Yongcheng, CAO Jun (Shipin Kexue, 2025)
High performance liquid chromatography with evaporative light-scattering detection (HPLC-ELSD) was adopted to determine 1,3-dioleoyl-2-palmitoylglycerol (OPO) and 1-oleoyl-2-palmitoyl-3-linoleoylglycerol (OPL) in 36 samples of 12 brands of formula milk powder for infants and young children at three age groups. Gas chromatography coupled with a hydrogen flame ionization detector was employed to measure the content of palmitic acid at the sn-2 position of triglyceride. Results revealed that fat contents in 32 samples significantly exceeded the nutrition label values. Among 18 samples of OPO-enriched milk powder, seven had OPO levels lower than the nutrition label values. OPO was detected in all 18 samples of non-OPO-fortified milk powder. OPO was more abundant than OPL in 34 samples. The proportions of saturated fatty acids (20.31%–50.12%) and monounsaturated fatty acids (33.13%–54.89%) in the formula were relatively high, whereas the proportion of polyunsaturated fatty acids (14.20%–31.76%) was slightly low. The relative content of sn-2 palmitic acid in the OPO-enriched milk powder was significantly higher than that in the non-OPO-fortified milk powder. This study provides valuable insights for research on the ‘humanization’ of lipids in infant formula.